Ovarian Tissue Cryopreservation in Children and Adolescents - Angeliki Arapaki; Panagiotis Christopoulos; Emmanouil Kalampokas; Olga Triantafyllidou; Alkis Matsas; Nikolaos F. Vlahos (MDPI AG, 2022)
Cancer during childhood and adolescence remains a major public health issue, affecting a significant portion of this age group. Although newer anti-cancer treatments have improved survival rates, this comes at a cost in terms of gonadotoxic effects. As a result, the preservation of fertility is important. Ovarian tissue cryopreservation, one of the newest methods, has some advantages, especially for prepubertal patients: no need for ovarian stimulation, thus, no further risk for estrogen-sensitive cancer types, and preservation of more and better-quality primordial follicles of the ovarian cortex. The most frequent indications include treatment with alkylating agents, ovarian-focused radiotherapy, leukemias, lymphomas, brain and neurological tumors, as well as Turner syndrome and benign hemoglobinopathies. An expected survival exceeding 5 years, the absence of systematic disease and an overall risk of premature ovarian insufficiency over 50% are among the criteria that need to be fulfilled in order for a patient to undertake this method. Orthotopic transplantation is more frequently used, since it can allow both live birth and the recovery of endocrine function. Reimplantation of malignant cells is always a major risk and should always be taken into consideration. Histological analysis, as well as immunohistochemical and molecular methods, are needed in order to improve the search for malignant cells before transplantation. Ovarian tissue cryopreservation appears to be a method with specific benefits, indications and risks which can be an important tool in terms of preserving fertility in younger women.